(Invited) Characterization of Buried Interfaces with Scanning Probe Microscopes. (26th April 2016) - Kopanski, Joseph J.; You, Lin; Li, Jennifer; Ahn, Jung Joon; Obeng, Yaw S.
Abstract : Scanning probe microscopes (SPMs) have some capability to image sub-surface structure, including the details of buried interfaces. This paper describes the theoretical and practical basis for obtaining information about shallow buried interfaces, subsurface compositional variations, and electrical potential variations with SPMs. Three techniques are discussed: scanning microwave microscopy (SMM) to image the capacitance of buried metal lines, scanning Kelvin force microscopy (SKFM) to image the potential of buried metal lines, and electric force microscopy (EFM) phase imaging to see buried interface surface roughness. COMSOL simulations of the SMM resonator response to small variations in tip-sample capacitance, explaining the contrast reversal phenomena, are described. SKFM and EFM images of NIST designed potential variation test structures show the potential of each technique for buried interface characterization.